Synthesis of the Complexes of S3N3Cl3 with Cadmium(II) and Mercury(II) - Rani, Shubha; Jadon, S.P.S. (Asian Journal of Chemistry, 2016)
Complexes of trithiazyl trichloride, S3N3Cl3, with Cd(CH3COO)2 and HgCl2 were synthesized and analyzed. On the basis of its IR and X-ray powder spectra, it is revealed that both the complexes have tetragonal geometry. The antibacterial and toxic effect of these complexes on the albino rats was also tested.